FESTIVAL AMÉRICA DO SUL E SUA IMPORTÂNCIA NA CONSOLIDAÇÃO DA IDENTIDADE TERRITORIAL FRONTEIRIÇA - SUZANA MENDES DIAS FLUD (2023)
Built by the Mato Grosso do Sul Culture Foundation and promoted by a network of actors and territorial agents, the South America Festival is an annual event held on the Brazil-Bolivia border, Corumbá/Ladário – Puerto Quijarro/Suárez corridor. This work aims to analyze the importance of the Festival in the consolidation and exposure of the border territorial identity. The research methodology is qualitative and involves analysis of documents and interviews together with the producers of the event and the attending public. We emphasize that the South America Festival, as an expression of South American culture, promotes encounter through celebration, joy, pleasure and what facilitates discussions on regional integration. The results of the research indicate the valorization and valuation of the border identity of a space composed of multiterritorialities, complex and multidimensional, which are intertwined. The identity constructed within this complexity is also hybrid, expressed by the distinction of being borderline, being South American, being Brazilian and being from Mato Grosso do Sul. The lived space, of intense daily relations between Bolivians and Brazilians, opens up and reveals itself, in its antagonisms: national identities used to differentiate the "we" from the "others" are intertwined with the regional identity, through the recognition of belonging and the relationships of affection that are established over the space. Keywords: Frontier, identity, territory, place, Pantanal, Festival South America..